Sakralitas Ritual Sedekah Bumi di Makam Kramat Batok Kabupaten Bekasi - Fatimah, Siti (Pascasarjana ISBI Bandung, 2019)
This study is aimed at revealing the process of the Sacredness of Ritual Sedekah Bumi in Kramat Batok, Bekasi. The study is done toward the structure of the ritual and the sacred elements of Batok sacred tomb, the offerings, ronggeng, masks, shadow puppets, a winding paddy (pocong padi) and buffalo slaughtering. This is to find out how people perceive the phenomena. The analysis of the sacredness uses Mircea Eliades view of sacredness and Victor Turners point on symbolic form. It is found out that the ways in which the community carries out its meaning are influenced by the social facts of the dominance of buhun (ancient) Sundanese culture, Pre-Islam and Hindu-Buddhist in the lives of Kramat Batok people for generations as a legacy from their ancestors.The analysis applying Jacob sumardjos proposition on paradox esthetic shows the harmony understanding between two contrary entities but completing each other. This is formulated as the three of Sundanese people, Tritangtu. The qualitative observation method is used in recording the activities of Kramat Batok community. By conducting interviews, field studies, literature studies and documentation studies, it is known that the Ritual Sedekah Bumi is a paradoxical cultural phenomenon in Kramat Batok community. This is because of the dualism belief in the system of thinking of the people, namely believing in the existence of Islam and its karuhun. The Sacredness of Ritual Sedekah Bumi has become part of the cycle of cultural events. This is as a form of expression of gratitute for the harvest. The ritual shows the primordial view of Kramat Batok community which is passed down from generation to generation, making the ritual activities maintained until todays.Keywords: Ritual, Sacred, Ngukup, Sedekah Bumi